THE INFLUENCE OF COMPANY IMAGE AND TRUST AND WORD OF MOUTH ON PURCHASING DECISIONS OF POSTAL EXPRESS SERVICES - Muhammad Arif; Adisya Nadira Putri (CERED Indonesia Institute, 2020)
The purpose of the research is to identify some of the factors that influence corporate image on purchasing decisions, the impact of trust on purchasing decision, And the impact of the corporate decisions and the trust and the word of mouth pn the purchasing of the service express at PT. Pos Indonesia (PERSERO) Medan 20000. In this research is a research technique used throught nonprobability sampling technique. Sampling which will be used in this research is purposive sampling with respondents' criteria that have ever used a pos service express. Data gathering technique used in the research are questionaires and data analysis techniques using SPSS (Statistical package for the social sciences) to draw a four hypotheses put forward in the research shows that (1) how corporate image affect positive and signifivant purchasing decisions,how corporate trust affect positive and signifivant purchasing decisions, (3) how word of mouth affect positive and signifivant purchasing decisions, (4) how corporate image and trust, and word of mouth affect positive and signifivant purchasing decisions.